Mechanism of Guilu Erxian ointment based on targeted metabolomics in intervening in vitro fertilization and embryo transfer outcome in older patients with poor ovarian response of kidney-qi deficiency type - Ma, Yingjie; Song, Jingyan; Cao, Xianling; Sun, Zhengao (Frontiers in Endocrinology, 2023)
To study the effect of Guilu Erxian ointment on the outcome of IVF-ET in older patients with hyporesponsive infertility of kidney-qi deficiency type, and to verify and analyze the mechanism of action of traditional Chinese medicine on improving older patients with hyporesponsive infertility of kidney-qi deficiency type from the perspective of metabolomics using targeted metabolomics technology, identify the related metabolic pathways, and provide metabolic biomarker basis and clinical treatment ideas for improving older patients with hyporesponsive infertility.